Pemberdayaan Santri Al-Rifa’ie Satu Melalui Ujian Kepesantrenan: Rekonstruksi Epistemologi Kepemimpinan Khidmah - Intan, Intan Karisma; Muhammad Husni (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service program aims to empower final-year students (santri) at Al-Rifa’ie 1 Islamic Boarding School through the epistemological reconstruction of "khidmah" leadership. The primary issue addressed is the gap between textual Islamic literature mastery (Nalar Bayani) and the students' lack of self-confidence and courage in leading public religious rituals, such as tahlil, istighosah, and serving as prayer imams. The mentoring strategy was implemented by integrating a Sanad-Centric approach (spiritual connection to the founders' lineage) and strengthening self-efficacy using audio imitation methods of the original voice of the boarding school's founder. Systematic steps included the distribution of pocketbooks as unification instruments, sanad transmission (ijazahan), collective practice, and rigorous evaluation stages involving supervised exams and public assessments through a random lottery system. The results indicate a significant transformation in the students' identity, where psychological barriers such as nervousness were successfully converted into mental stability and social legitimacy. This program has successfully established uniform alumni competency standards that are spiritually authoritative and technically prepared to serve as religious ritual leaders within the community.